Reproductive traits and spawning activity of striped eel catfish (Plotosidae) in Kolono Bay, Indonesia - Asriyana Asriyana; Halili Halili (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Asriyana A, Halili H. 2021. Reproductive traits and spawning activity of striped eel catfish (Plotosidae) in Kolono Bay, Indonesia. Biodiversitas 22: 3020-3028. Reproduction is a natural process for a species to ensure its sustainability in nature. This study aimed to investigate the reproductive traits and spawning activity of the striped eel catfish in Kolono Bay, South Konawe District, Southeast Sulawesi, Indonesia. A total of 965 individuals were collected monthly from June 2020 to May 2021 by using bottom experimental gillnets. Spent/spawning stages of the male and female fish were found during the East season (June-August). The proportions of the spent/spawning stages of male and female fish were 60% and 55.56% and the values of the gonadal somatic index were 1.19 ± 0.53 and 2.19 ± 3.47, respectively during the East season, indicate occurring the peak spawning in this season. Females matured gonads more rapidly at 198.3 mm compared to males at 224.5 mm. Female fecundity was 1,730 ± 390 eggs, with an egg diameter of about 0.11-1.35 mm. Striped eel catfish is a total spawner fish that has one mode of egg distribution pattern. During the East season, it needs protection for spawning. The findings will help in designing effective management and developmental strategies to conserve the striped eel catfish population in the future.